Literature Review: Efektivitas Metode Pembelajaran Inovatif dalam Pendidikan Biologi - Karmana, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This research aims to examine the effectiveness of innovative learning methods in biology education through a literature review. Innovative learning methods, which include project-based approaches, collaborative learning, and the use of digital technology, have become a major focus in improving the quality of education at various levels. By analyzing various studies and relevant literature, this research evaluates the impact of the method on conceptual understanding, student motivation, and learning outcomes in biology subjects. The results of the review show that the application of innovative learning methods not only increases student engagement, but also supports the development of critical and analytical thinking skills. Additionally, this research identifies challenges faced by educators in implementing innovative methods, as well as recommendations for better educational practices in the future. These findings are expected to provide a significant contribution to curriculum development and teaching strategies in biology education.